Developmental Foreign Accent Syndrome: Report of a New Case - Keulen, Stefanie; Mariën, Peter; Wackenier, Peggy; Jonkers, Roel; Bastiaanse, Roelien; Verhoeven, Jo (Frontiers in Human Neuroscience, 2016)
This paper presents the case of a 17-year-old right-handed Belgian boy with developmental FAS and comorbid developmental apraxia of speech (DAS). Extensive neuropsychological and neurolinguistic investigations demonstrated a normal IQ but impaired planning (visuo-constructional dyspraxia). A Tc-99m-ECD SPECT revealed a significant hypoperfusion in the prefrontal and medial frontal regions, as well as in the lateral temporal regions. Hypoperfusion in the right cerebellum almost reached significance. It is hypothesized that these clinical findings support the view that FAS and DAS are related phenomena following impairment of the cerebro-cerebellar network.